Molecular genetic analysis of the ICE1 gene in Arum korolkowii Regel - Aigerim Yeginbay; Gulzhaina Alpamyssova; Zhanar Yelemanova; Zaure Narymbayeva; Amina Daulbay; Rakhat Pernebekova; B. A. Abduvaliev; Altunbek Burabaev; Assilbek Burabaev; Abdujalil Narimanov (Caspian Journal of Environmental Sciences)
The paper presents a molecular genetic analysis of the expression of the ICE 1 gene Arum korolkowii Regel involved in the abiotic stress response in the Korolkov Aronnik in cold and frost conditions. The classical PCR method was used to identify the ICE 1 gene in Aronnik Korolkov and sequenced this site to determine the uniqueness of this gene. When stress is induced, increased expression of the studied gene is shown. It has been proved that the expression of this gene in Aronnik Korolkov begins already at the stage of acclimatization.